Perancangan Sistem Pencatatan Akuntansi dengan Menggunakan Aplikasi Microsoft Access pada Yudi Tas Grosir - Serly Serly; Jennifer Jennifer (Universitas Internasional Batam, 2021)
Yudi Tas Grosir is an online trading business that sells imported bags by live streaming on social media. Yudi Tas Grosir has been established two years, and during that time the business calculates profit and loss by recording total expenses and total incomes. The business doesn’t have a proper accounting recording system. This causes the information obtained from manual recording is inaccurate and less efficient. Based on this problem, the author intends to take a role in social engagement by creating a computerization accounting recording system that is expected to be reliable by the business owners to carry out the good and proper operational accounting records so that the business owner can get all the financial information accurately. Therefore, the author will explore, study, and find the right solution to all problems. In tracing business problems, the author will directly visit business owners, gather business information by conducting interviews with owners,s and monitoring business operational activities. Reports generated from the designed system are the income statement, statement of financial position, account payable, and receivable reports. This accounting system is expected to bring significant changes to the business owner.